2021
DOI: 10.1016/j.imu.2021.100705
|View full text |Cite
|
Sign up to set email alerts
|

Data interpretation and visualization of COVID-19 cases using R programming

Abstract: Background Data analysis and visualization are essential for exploring and communicating medical research findings, especially when working with COVID records. Results Data on COVID-19 diagnosed cases and deaths from December 2019 is collected automatically from www.statista.com , datahub.io, and the Multidisciplinary Digital Publishing Institute (MDPI). We have developed an application for data visualization and analysis of several indicators… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Finally, in our context of a comparative study, considering different post-COVID-19 groups by severity of a previous SARS-CoV-2 infection and different medical treatment protocols may be prognostically important, as Rimal et al ( 2021 ) showed in the area of data analysis and visualization, which are essential for exploring and communicating medical research findings, especially when examining COVID-19 records.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, in our context of a comparative study, considering different post-COVID-19 groups by severity of a previous SARS-CoV-2 infection and different medical treatment protocols may be prognostically important, as Rimal et al ( 2021 ) showed in the area of data analysis and visualization, which are essential for exploring and communicating medical research findings, especially when examining COVID-19 records.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, individuals who recovered from COVID-19 had a later chronotype than those without a history of COVID-19 (Han et al, Tedjasukmana et 2023). in our context of a comparative study, considering different post-COVID-19 groups by severity of a previous SARS-CoV-2 infection and different medical treatment protocols may be prognostically important, as Rimal et al (2021) showed in the area of data analysis and visualization, which are essential for exploring and communicating medical research findings, especially when examining COVID-19 records.…”
Section: Discussionmentioning
confidence: 99%